Estimation of Coverage Interval of Serum β-Carotene among Bengali Population - Sanghamitra Chakraborty; Indranil Chakraborty (Journal of Clinical and Diagnostic Research, 2019)
Introduction: The reference interval guides the clinician in interpreting the clinical test reports and classifying the subjects as healthy or diseased. The reference values of the common laboratory analytes vary due to immense diversity in race, ethnicity, genetic pattern and food habits. Recommendations from international body’s mandates for every laboratory to establish its own reference values for the population it serves for correct interpretation of test results. A series of recent research indicates the protective role of the antioxidant vitamin β-carotene against both exogenous and endogenous free radicals. These free radicals mediated damage to intracellular organelles and cell membrane lead to mutations, coronary artery disease, autoimmune diseases and malignancy. Aim: To determine the coverage interval of serum β-carotene in Bengali population and to compare them with the reference interval of other population. Materials and Methods: The present non-interventional, crosssectional study was conducted in Medical College and Hospital, Kolkata, from January 2012 to January 2013. Based on IUPAC clinical division technical report with 0.95 confidence interval, 0.95 coverage interval and coverage uncertainty of 0.049, 71 individuals were included in the study. Blood samples were collected from 71 (34 male and 37 female) healthy volunteers (postgraduate trainee students, DMLT students, nursing staff and undergraduate students) at random as per recommendation of IUPAC Clinical Chemistry Division for calculation of coverage interval. The β-carotene levels were measured by Bradley and Hornbeck (1973) method spectrophotometerically. The Kolmogorov-Smirnov test was used to check for normal distribution. Results: The mean age and weight of the study population 28.49±9.49 years and 62.9±11.58 kg respectively. The mean concentration of serum β-carotene was found to be 140.12 μg/dL (2.62 μmol/L) which was much higher than other populations. Conclusion: The study conducted to determine the coverage interval of β-carotene, a replica of reference interval with small number of values, from the general healthy population. The reference values of Bengali population was found to be, much higher than Kuwaiti, European, Chinese, Vietnamese and Thailand populations.